2005
DOI: 10.1002/ejoc.200500138
|View full text |Cite
|
Sign up to set email alerts
|

Novel Chiral (Salen)MnIII Complexes Containing a Calix[4]arene Unit as Catalysts for Enantioselective Epoxidation Reactions of (Z)‐Aryl Alkenes

Abstract: New asymmetric (salen)Mn III and UO 2 complexes containing a calix [4]arene unit in the ligand framework were synthesized. The UO 2 complexes were characterized by 1 H-, 13 C-, 2D TOCSY and T-ROESY NMR spectroscopy. Furthermore, the structure of one UO 2 complex was determined by singlecrystal X-ray analysis. The data showed that UO 2 complexes, which can be considered in first approximation models of the Mn=O oxidant active species, possess a chiral pocket and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 33 publications
4
53
0
Order By: Relevance
“…These findings seem to indicate that the carboxylate anion of the amino acid behaves as the hard chloride in binding the uranyl metal center driving the molecular recognition event. [10,17] To the best of our knowledge, this uranyl complex represents the first hitherto reported chiral receptor able to recognize and strongly bind carboxylate anions of amino acids. NMR spectroscopic data support this conclusion.…”
Section: Resultsmentioning
confidence: 98%
“…These findings seem to indicate that the carboxylate anion of the amino acid behaves as the hard chloride in binding the uranyl metal center driving the molecular recognition event. [10,17] To the best of our knowledge, this uranyl complex represents the first hitherto reported chiral receptor able to recognize and strongly bind carboxylate anions of amino acids. NMR spectroscopic data support this conclusion.…”
Section: Resultsmentioning
confidence: 98%
“…11 Condensation of 1,1 0 -diaminoferrocene with salicylaldehydes gave achiral derivatives whose Mg, Ti and Zr-complexes have been structurally characterized 12 and more recently the synthesis, but not their use as catalysts, of some planar chiral ferrocene salen-type ligands has been reported. 13 Our interest in the development of new ligands for the Mn-catalyzed enantioselective epoxidation of olefins 14 prompted us to plan the synthesis of two novel ferrocenyl derivatives L1 and L2, possessing central chirality, C 2 -symmetry and the structural features of the 'salen-type' ligands, in order to test their catalytic activity in this reaction and here we report the obtained results ( Fig. 1).…”
Section: Introductionmentioning
confidence: 94%
“…The stereochemistry and conformation of di-Schiff bases containing calix [4]arene unit U(IV) complexes have been deduced on the basis of the 2D TOCSY and T-ROESY measurements. 116 Amato et al 117 analysing the T-ROESY data have shown that formation of the uranyl(VI) complex maintained the symmetrical structure of the Schiff base containing two biphenyl units. The lack of dipolar contacts between aromatic rings as well as between aromatic protons and isohexyloxy substituents suggested the presence of less hindered discshaped complex conformation in solution.…”
Section: U(iv) Complexesmentioning
confidence: 97%